The Effect of Flaxseed (Linum usitatissimum) Ethanol Extract on LDL Cholesterol Levels and Foam Cell Number in the Aorta of Male Wistar Rats (Rattus norvegicus) Fed A High-Fat and High-Fructose Diet - Marzha Marcella; Desak Made Wihandani; I Gusti Ayu Artini; I Wayan Juli Sumadi; I Made Pande Dwipayana; Ni Putu Sriwidyani (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2026)
A diet high in saturated fat and fructose leads to dyslipidemia, increasing atherosclerosis risk. Although lipid-lowering medications are available, they have certain limitations. Flaxseed, rich in ALA, lignans, and phytosterols, may improve lipid profiles and act as an antioxidant. This study evaluated the effectiveness of flaxseed in preventing LDL cholesterol elevation and aortic foam cell formation in male Wistar rats fed a high-fat, high-fructose (HFHF) diet.This actual experimental study used a post-test-only control group design for 35 days. Twenty-five male Wistar rats were randomly assigned to five groups: N (normal control, standard diet), K (negative control, HFHF diet), and three treatment groups (P1, P2, P3, HFHF diet) receiving flaxseed ethanol extract at doses of 200, 400, and 800 mg/kgBW/day. LDL cholesterol levels (mg/dL) and aortic foam cell counts (cells/HPF) were measured. Data were analyzed using Shapiro-Wilk and Levene tests for normality and homogeneity, followed by one-way ANOVA, Kruskal-Wallis, and Tukey-HSD post hoc tests. LDL cholesterol levels in groups N, P1, P2, and P3 were significantly lower than in group K (p = 0.007), with P2 showing the most significant inhibition (p = 0.035). Foam cell counts were lower in treatment groups than in group K (p = 0.257), but no significant differences were found among them. Flaxseed (Linum usitatissimum) ethanol extract at 400 mg/kgBW/day was the most effective in preventing an increase in LDL cholesterol. However, the extract at all three doses was ineffective in preventing an increase in aortic foam cells in male Wistar rats (Rattus norvegicus) fed an HFHF diet.